Urinary leukotriene E4 at 12 months and influencing factors - Stencel-Gabriel, K; Czuba, Z; Gabriel, I; Majda, A (Journal of Education, Health and Sport, 2016)
Stencel-Gabriel K, Czuba Z, Gabriel I, Majda A. Urinary leukotriene E4 at 12 months and influencing factors. Journal of Education, Health and Sport. 2016;6(1):197-206. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.45337 http://ojs.ukw.edu.pl/index.php/johs/article/view/45337 https://pbn.nauka.gov.pl/works/709857 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 15.12.2015. Revised 12.01.2016. Accepted: 25.01.2016. Urinary leukotriene E4 at 12 months and influencing factors Stencel-Gabriel K ( 1 ), Czuba Z ( 2 ), Gabriel I ( 3 ), Majda A ( 1 ) 1. Departament of Pediatrics, Bytom, Medical University of Silesia 2. Departament of Microbiology and Immunology, Zabrze, Medical University of Silesia 3. Department of Gynecology, Obstetrics and Oncological Gynecology, Bytom, Medical University of Silesia Corresponding author: Krystyna Stencel-Gabriel ul. Batorego 15 41-902 Bytom Keywords: leukotriene E4, infants, allergy, urine. Summary Objective LTE4 is the end point of cysLTs pathway and its only stable product. Its role was discussed in asthma and AEDS. We aimed to investigate the impact of genetic and environmental factors ( sex, maternal positive family atopy history, breastfeeding, passive smoking and pet exposure ). 60 newborns ( including 30 boys ) were enrolled in the study. Each child was examined at 12 months and urine samples for urinary LTE4 measurement were collected. All samples were processed using ACETM Enzyme Immunoassay Kit ( Cayman Chemical, Ann Arbor, MI, USA ). The mean level of urinary LTE4 at 12 months was 186,99 pg/ml ( median: 159,0; CI 95%: 157,79- 221,59 ). The Shapiro- Wilk test showed that the distribution of the levels of urinary LTE4 were abnormal. 12- month- old girls had higher urinary LTE4 levels than boys ( mean: 270,50 vs. 193,55 ), but maternal positive atopy history, pet exposure, tobacco smoking or length of breastfeeding had no impact on urinary LTE4 excretion. Conclusions In conclusion, most of genetic or environmental factors do not change levels of urinary LTE4 in infants.